Analysis of digital marketing and its effect on the positioning of Peruvian universities in 2023 - Canaza Calsina, Yilda Lisset (2024)
Introduction/Objective: Any change and strategic advertising and/or commercial plan- ning carried out by means of digital media is called digital marketing, which helps uni- versities to position themselves, which is why Peruvian universities create and share relevant content on digital platforms. The objective of this study is to determine how digital marketing affects the positioning of Peruvian universities. Methodology: A quantitative approach and a deductive, non-experimental research de- sign were used. A survey instrument was applied to 433 students studying at the Uni- versidad Continental (located in Arequipa, Cusco, Huancayo, and Lima), and the Partial Least Squares Structural Equation Modelling (PLS-SEM) model was used, a multivariate statistical method for analysing the independent variable of digital marketing and the dependent variable of positioning. Results: The study found that the variation in units of Customer Acquisition, Customer Conversion, and Content Distribution generates a variation in positioning of 0.36, 0.24, and 0.20 units, respectively. Conclusions: Customer Acquisition is the most determining factor for positioning, fol- lowed by Conversion and, finally, Content Distribution. Additionally, it is established that Customer Acquisition primarily impacts the Service level, while Content Distribution has a greater influence on the Staff level.